2019
DOI: 10.1371/journal.pone.0220990
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and use of antibiotics in Thailand: A 2017 national household survey

Abstract: Background The Thailand National Strategic Plan on Antimicrobial Resistance (AMR) 2017–2021, endorsed by the Thai Cabinet in 2016, aims to increase public knowledge about antibiotics and AMR awareness by 20% by 2021. This study assesses the prevalence of antibiotics use, clinical indications and sources; knowledge and access to information related to antibiotics and AMR; and factors related to level of knowledge and access to information among Thai adult population. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
48
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 22 publications
(19 reference statements)
11
48
2
4
Order By: Relevance
“…Like similar surveys from other LMICs, including those in urban settings, our data indicate high levels of antibiotic consumption among rural community members [17,[33][34][35][36]. Globally, national-level rates of antibiotic resistant microbes/infections are closely correlated with human antibiotic consumption rates [37,38].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Like similar surveys from other LMICs, including those in urban settings, our data indicate high levels of antibiotic consumption among rural community members [17,[33][34][35][36]. Globally, national-level rates of antibiotic resistant microbes/infections are closely correlated with human antibiotic consumption rates [37,38].…”
Section: Discussionsupporting
confidence: 73%
“…This problem is faced by all similar surveys of rural LMIC communities, with levels of awareness varying substantially but typically being moderate to low [30][31][32], although comparisons are difficult. Some similar surveys do not initially check awareness and apparently rely on respondents who are not aware of antibiotics to select "don't know" type responses [19,33,34], which may lead to increased bias. Therefore, our results, and those of similar studies looking at antibiotic knowledge in more detail, highlight that there is a huge amount of work to be done on educating rural populations in LMICs about antibiotics and appropriate practices.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a 5-year analysis on antibiotic resistance was reported even in high-standard hospitals, with several antibiotic resistances found particularly among patients who had a history of misusing antibiotics prior to being admitted to the hospital, especially those who had poor knowledge of antibiotic use [25]. Additionally, a study in Thailand reported that people who had higher educational levels and those with greater wealth were associated with having antibiotic drug resistance [8].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Thailand launched a 5-year national strategic plan to reduce antimicrobial resistance (NSP-AMR:2017-2021) aimed at reducing antibiotic misuse by enhancing public awareness and reducing antibiotic resistance in the Thai population [6,7]. Commonly, Thai people are able to access antibiotics without prescriptions, such as through buying drugs from private drugstores or pharmacies, including from a small grocery in a community [8]. Moreover, self-medication is a common health behavior in Thai individuals [9].…”
Section: Page 3/25mentioning
confidence: 99%
“…2 - 4 Half (50.3%) of household members who used antibiotics reportedly obtained the drugs from public hospitals and health facilities. 5 Antibiotic prescribing rates, however, tend to vary widely across hospitals. 2 Due to concerns regarding antibiotic overuse, an action research program aiming to change the perceptions and prescribing behavior of physicians, known as the “Antibiotic Smart Use (ASU)” program, was trialed in 2007-2012.…”
Section: Introductionmentioning
confidence: 99%